METHODICAL APPROACHES TO ASSESSING THE LEVEL OF FINANCIAL CAPACITY OF TERRITORIAL COMMUNITIES - PRIKHNO, Iryna; PRODANOVA, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the budgets of territorial communities in 2019-2022, in particular, the revenues of the General Fund and the expenditures of the general fund. It has been found that the revenues of territorial community budgets are generated at a faster rate than financial resources are spent. Generalization of educational methodological provisions on the diagnosis of budget efficiency of territories was completed, on which a system of existing directions of diagnostics, criteria and indicators is schematically presented. The current methods of assessing the financial capacity of territorial communities, in particular, the methodology of measuring the financial capacity of the territorial communities of the regional centers of Ukraine during 2018-2021 (9 months) and the draft methodological recommendations for assessing the level of financial capacity of territorial communities were analyzed. The algorithm for calculating the integral index of development of the potential of the territorial community is investigated, which provides for the calculation of indicators of development of territories. Calculations of financial capacity of territorial communities according to different methods on the example of territorial communities of Cherkasy region were performed. The analysis of the level of financial capacity of the Cherkasy territorial community in 2021 found that the level of financial capacity of the Cherkasy territorial community corresponds to the optimal level, as evidenced by the generalized indicator of the level of financial capacity of 1.36. It has been revealed that these techniques do not allow quantifying the level of financial capacity and calculating the percentage of increasing the financial capacity of the territorial community. The directions of improvement of methodological approaches to assessing the level of financial capacity of territorial communities are proposed.